Exiliados, expatriados e integrados : chilenos en Costa Rica 19732018 - Oliva Medina, Mario (Heredia Editorial Universidad Nacional (EUNA), 2020)
The closest figures regarding the number of exiles, expatriates and integrated individuals in the case of Chileans in Costa Rica, which this book deals with, range from the 3,000 people who entered the country from 1973 to at least the end of that decade and part of the 1980s, which is combined with a process of return, or better said, of de-exile (repatriation) in the last years of the 1980s and following, although the chronological arc of this text covers practically four decades.
Spanish
Keywords: Social & cultural history; Exile; Chile; Costa Rica; Solidarity; Social aspects; Political aspects; Immigration; Higher education; Escámez Carrasco, July 1925-2015; Dictatorship